Protective Effects of Crocetin on Arsenic Trioxide-Induced Hepatic Injury: Involvement of Suppression in Oxidative Stress and Inflammation Through Activation of Nrf2 Signaling Pathway in Rats - Liu Y; Liang Y; Zheng B; Chu L; Ma D; Wang H; Chu X; Zhang J (Dove Medical Press, 2020)
Yanshuang Liu,1,2,* Yingran Liang,3,* Bin Zheng,3 Li Chu,3 Donglai Ma,3 Hongfang Wang,3 Xi Chu,4 Jianping Zhang2,5 1Department of Diagnostics, School of Integrated Chinese and Western Medicine, Hebei University of Chinese Medicine, Shijiazhuang, Hebei, 050200, People’s Republic of China; 2Hebei Key Laboratory of Integrative Medicine on Liver-Kidney Patterns, Shijiazhuang 050200, Hebei, People’s Republic of China; 3Department of Pharmaceutics, School of Pharmacy, Hebei University of Chinese Medicine, Shijiazhuang, Hebei, 050200, People’s Republic of China; 4Department of Pharmacy, The Fourth Hospital of Hebei Medical University, Shijiazhuang, Hebei, 050011, People’s Republic of China; 5Department of Pharmacology, School of Basic Medicine, Hebei University of Chinese Medicine, Shijiazhuang, Hebei, 050200, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xi ChuThe Fourth Hospital of Hebei Medical University, Shijiazhuang 050011, Hebei, People’s Republic of ChinaTel/Fax +86 311 86095324Email chux2014@126.comJianping ZhangSchool of Basic Medicine, Hebei University of Chinese Medicine, Shijiazhuang 050200, Hebei, People’s Republic of ChinaTel/Fax +86 311 89926719Email zhangjianping14@126.comPurpose: Arsenic trioxide (ATO) has been shown to induce hepatic injury. Crocetin is a primary constituent of saffron, which has been verified to have antioxidant and anti-inflammatory effects. In the current experiment, we evaluated the efficacy of crocetin against ATO-induced hepatic injury and explored the potential molecular mechanisms in rats.Methods: Rats were pretreated with 25 or 50 mg/kg crocetin 6 h prior to treating with 5 mg/kg ATO to induce hepatic injury daily for 7 days.Results: Treatment with crocetin attenuated ATO-induced body weight loss, decreases in food and water consumption, and improved ATO-induced hepatic pathological damage. Crocetin significantly inhibited ATO-induced alanine aminotransferase (ALT), aspartate aminotransferase (AST), and alkaline phosphatase (ALP) increases. Crocetin prevented ATO-induced liver malondialdehyde (MDA) and reactive oxygen species (ROS) levels. Crocetin abrogated the ATO-induced decrease of catalase (CAT) and superoxide dismutase (SOD) activity. Crocetin was found to significantly restore the protein levels of interleukin 6 (IL-6), interleukin 1β (IL-1β), and tumor necrosis factor-alpha (TNF-α). Furthermore, crocetin promoted the expression of nuclear factor erythroid 2 related factor 2 (Nrf2), heme oxygenase-1 (HO-1), and NADP(H): quinone oxidoreductase 1 (NQO1).Conclusion: These findings suggest that crocetin ameliorates ATO-induced hepatic injury in rats. In addition, the effect of crocetin might be related to its role in antioxidant stress, as an anti-inflammatory agent, and in regulating the Nrf2 signaling pathway.Keywords: crocetin, arsenic trioxide, hepatotoxicity, oxidative stress, inflammation, Nrf2 signaling pathway